The Role of Bone Scintigraphy and Parathyroid Scintigraphy on Multiple Osteolytic Lesions Which Misdiagnosed as Primary Bone Tumor (Giant Cell Tumor) - Prasetyo, Nora A.; Darmawan, Budi; Affandi, Erwin; Kartamihardja, A. Hussein S. (Medicinus, 2022)
Brown tumor is a non-neoplastic lesion that resulting from abnormal bone metabolism. It can be manifest in prolonged or untreated hyperparathyroidism. The clinical symptoms, radiological and histopathological examination were similar with giant cell tumor and can be mimicking metastases; or even misdiagnosed with giant cell tumor and mistreated the patient. Biochemical examination of calcium levels and parathyroid hormone should be included in the routine assessment of patients with multiple osteolytic lesions. A multidiscipline approach is needed.Throughout this case report, we would like to report the important role of Nuclear Medicine and Molecular Theranostic imaging modality in 38-year-old male with multiple osteolytic lesions, which was first diagnosed as giant cell tumor and differential diagnosis bone metastases but turnout to be a metabolic bone disease (brown tumor) with parathyroid adenoma as etiology.